Oxidative response of Vitis vinifera cells elicited with Phaeomoniella chlamydospora - Lima, M. R. M. (2007)
Esca is a destructive disease that affects vineyards leading to important losses in wine production, which incidence has dramatically increased during the last few years. Phaeomoniella chlamydospora (Pc) is a fungus frequently associated with esca and grapevine decline. Information on the interaction of this fungus with Vitis plants is scarce. To study early defense mechanisms, namely the oxidative response, of Vitis plants to Pc we utilized in vitro cell suspension cultures of V. vinifera cv. Vinhão (Vv) and a Pc elicitor (hydrolyzed extract).